Applicability of ERA5 Reanalysis Data in Simulating Water Level of Medium and Small-Scale Reservoirs:a Case Study of Changjiang Reservoir - CHEN Junlai; ZHANG Zhouwen; CHEN Weihua; HU Xubao (Renmin Zhujiang)
The water level in front of the reservoir is important observation data for medium and small-scale reservoir basins.The reanalysis of this data provides optional schemes for the simulation of water levels in medium and small-scale reservoirs,but its applicability still needs to be evaluated.This study took the Changjiang Reservoir Basin in Zhongshan City as an example to assess the accuracy of ERA5,ERA5-Land reanalysis precipitation,and potential evapotranspiration data under different time scales.Based on the three-source Xinanjiang model coupled with reservoir water management,this study set up different input scenarios and analyzed the applicability of ERA5,ERA5-Land precipitation,and potential evapotranspiration data in water level simulation of the reservoir.The results show that at the annual,monthly,and daily scales,the two reanalysis precipitation data in the study area are consistent with the observed precipitation,while the consistency of the reanalysis potential evapotranspiration data with the observed evaporation is weaker.In the seven scenarios of water level simulation,the rate-periodic NSE can all reach 0.6 or more,and there are differences in the input during the validation period.The adaptability of ERA5 reanalysis data is better than that of ERA5-Land,and the reanalysis potential evapotranspiration data can be used as an alternative input for the model evaporation data,but the reanalysis precipitation data is not suitable for direct use in the model input.This study can provide a reference for the application of ERA5 and ERA5-Land data in the simulation and forecasting of reservoir water levels with insufficient data and provide a feasible scheme for the construction of reliable hydrological models in medium and small-scale reservoir basins.